PERCEPATAN LEGALITAS DAN DIGITALISASI UMKM DI KELURAHAN PLOSO OLEH MAHASISWA KKN BELA NEGARA - Rishad Daristama Baihaqi; Muhammad Bhirawa Dwi Atma Citalada; Nasywa Shabrina Khunaifi (ABIDUMASY, 2026)
Abstract: The community service program entitled "Digitalization and Business Legality of MSMEs" was part of the Thematic Community Service (KKN) on National Defense conducted by UPN "Veteran" East Java students in Ploso Urban Village, Tambaksari District, Surabaya. This program was motivated by the low level of business legality and digital adoption among Micro, Small, and Medium Enterprises (MSMEs). It aimed to enhance legal registration and digital readiness of MSMEs in alignment with SDG 8. Community partners included local MSME actors, village officials, and the Halal Product Process Assistance Institution (LP3H). The method involved field surveys, technical assistance, and direct facilitation for OSS registration, Google Maps business listing, QRIS activation, and halal certification. As a result, dozens of MSMEs obtained Business Identification Numbers (NIB), listed their businesses online, adopted digital payment, and began halal certification through the free self-declare scheme. The outcomes highlight that collaborative and educational approaches are essential to empower MSMEs in facing digital and regulatory transitions. This initiative contributes significantly to strengthening community-based local economic resilience.